Knowledge of gestational diabetes mellitus among pregnant women in a semiurban hospital - A cross -sectional study - Karthiga Prabhu J; Surya Deepthi Kondamuri; Sunita Samal; Maitrayee Sen (Elsevier, 2021)
Background: Prevalence of gestational diabetes is on the rise throughout the world, particularly in south east Asia. Gestational diabetes affects both present and future generations. The present study was conducted to study the knowledge about GDM, among antenatal women in a tertiary care hospital located in semiurban area. Methodology: In this cross-sectional questionnaire based study, a prevalidated questionarre with 18 questions regarding general awareness and knowledge about risk factors of GDM, screening of GDM, treatment modalities, immediate and long term consequences of GDM were used. Participants were divided into 3 groups based on knowledge score - good (score>12), fair (score 7-12) and poor (score≤6) knowledge. Results: Among the 200 study participants, only 92 (46%) knew that diabetes can occur for the first time during pregnancy. Good knowledge about GDM was present in 103 (51.5%), fair knowledge in 68 (34%) and poor knowledge in 29 (14.5%). Among the knowledge about risk factors of GDM, family history of diabetes was considered as a major risk factor (84.5%) followed by obesity (53.5%). Only 34.5% of patients were aware that GDM screening should be done for all antenatal women. Knowledge about fetal and neonatal complications was seen in only 30-50% of participants. Education and family history of diabetes were found to be significantly associated with better knowledge score (p = 0.0002, p = 0.03 respectively). Conclusion: Awareness about effect of GDM on the neonate and the mother should be created to improve GDM screening especially in non graduates and those residing in rural areas. Grass root level workers should be more involved in spreading awareness to all antenatal mothers from rural areas.